Clinical and Course Indicators of Bipolar Disorder Type I with and without Opioid Dependence - amir shabani (Journal of Research in Medical Sciences, 2010)
Abstract

BACKGROUND: The existing evidence about the clinical situations of the bipolar patients with opioid dependence is scarce. The present study was carried out to compare the clinical features and course of the bipolar disorder type I regarding the two subgroups of opioid dependent and non-dependent.

METHODS: 178 adult inpatients with bipolar disorder type I consecutively referred to the Iran Hospital of Psychiatry, Tehran, Iran, from January 2008 to January 2009 were enrolled in the study. The Persian Structured Clinical Interview for DSM-IV axis I disorders (SCID-I), HDRS-17, and Y-MRS were administered for all patients. Other clinical information was gathered through the face-to-face interviews with the probands and the hospital records. The t-test, chi-square test, and logistic regression were used to analyze the data.

RESULTS: The probands were 33.6 (±11.1) years old and mostly male. Among the evaluated indices, the factors gender, anxiety disorders comorbidity, non-adherence, and positive family history were different significantly and independently from the other studied factors between opioid dependent and non-dependent bipolar patients.

CONCLUSIONS: Despite some differences, the opioid dependent and non-dependent bipolar patients did not have any significant difference regarding most of the tested clinical and coarse indices.